Malaria-related hospitalization during childhood in Papua, Indonesia: A retrospective cohort study - Douglas, Nicholas M. (PLoS One, 2020)
BACKGROUND: In endemic regions, the age distribution of malaria varies according to the infecting Plasmodium species. We aimed to delineate the pattern of malaria-related hospitalization from birth in Timika, Papua–an area co-endemic for P. falciparum and P. vivax METHODS: Between April 2004 and December 2013, infants born at Mitra Masyarakat Hospital, or presenting within the first 7 days of life, were enrolled retrospectively into a cohort study and followed passively using routinely-collected hospital surveillance data. Outcomes were stratified by the presence or absence of Plasmodium parasitemia and included re-presentation to hospital, requirement for hospital admission and death. RESULTS: Overall, 11,408 infants were enrolled into the cohort. Median follow-up was 4.3 (maximum 9.7) years. In total, 7,847 (68.9%) infants made 90,766 re-presentations to hospital, 18,105 (19.9%) of which were associated with Plasmodium parasitemia. The incidence of re-presentations with malaria during the first year of life was 213 per 1,000 person-years (py) for P. vivax and 79 per 1,000py for P. falciparum (Incidence Rate Ratio (IRR) = 2.69, 95% Confidence Interval (95%CI): 2.48–2.92). After the age of 5 years, the incidence of P. vivax had fallen to 77/1,000py and the incidence of P. falciparum had risen to 95/1,000py (IRR = 0.80, 95%CI: 0.73–0.88). Overall, 79.7% (14,431/18,105) of malaria re-presentations were recurrences rather than initial infections. Malaria accounted for 31.7% (2,126/3,120) of all hospital admissions. The infant mortality rate in this study was 52 deaths per 1,000 live births. Beyond the early neonatal period, 13.4% of deaths were associated with Plasmodium parasitemia. CONCLUSIONS: In Papua, Indonesia, malaria is a major cause of hospital presentation and admission in early life. The initial predominance of P. vivax over P. falciparum inverts after five years of age. Malaria is directly associated with nearly one in seven deaths after the early neonatal period.